A Systematic Meta-analysis of Prosthetic-Based Breast Reconstruction in Irradiated Fields With or Without Autologous Muscle Flap Coverage. Issue 1 (January 2016) - Fischer, John P.; Basta, Marten N.; Shubinets, Valeriy; Serletti, Joseph M.; Fosnot, Joshua
Abstract : Background: The popularity of implant-based breast reconstruction, along with the well-established benefits of radiation therapy, unfortunately can lead to device placement into irradiated fields. Here, we compare prosthetic reconstructions with latissimus dorsi (LD) or subpectoral implants alone via systematic meta-analysis. Methods: A literature search identified articles involving prosthetic-based breast reconstruction in the setting of prior irradiation with or without an LD flap. The primary outcomes of interest, including device loss, capsular contracture, reoperation, and infection, were analyzed via head-to-head meta-analysis. Results: Thirty-one studies and 1275 reconstructions were included. Average age was 48.9 years and average follow-up was 42.8 months. The head-to-head odds ratio for implant loss with implant-only versus LD-assisted reconstruction was 4.33 ( P = 0.0003, I 2 = 7%), favoring LD-assisted reconstruction. Implant loss in pooled analysis was 5.0% for LD-assisted reconstruction and 15.0% for implant-only ( P < 0.001). Conclusions: In previously irradiated fields, prostheses placed with an LD flap demonstrated a clinically significant reduction in device loss, infection, and reoperation.